Pengaruh Penambahan Daun Kelor (Moringa Oleifera) Terhadap Daya Terima Sempol Ayam - Nelia Jose Ximenes; Arya Ulilalbab; Cucuk Suprihartini; Enggar Anggraeni (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2021)
Moringa Oleifera contains vitamin A 4 times greater than carrot, vitamin C 7 times greater than orange, calcium 4 times greater than milk, protein 2 times greater than milk also, so does the potassium content of moringa leaves 3 times more than banana. In fact, the use of Moringa leaves in this time is not maximized. Based on the potentiality that is contained in Moringa leaves, it is necessary to do more innovation to process moringa leaves, one of them is by making it health food such as sempol. Sempol is one of the street foods from Malang. Sempol is a food that is made of mashed chicken which is skewered like satay and fried with stir egg. The purpose of this study is to know the effect of addition moringa oleifera toward accepatability of sempol. This research was conducted in food technology laboratory of Nutrient Academy Karya Husada Kediri on June using experimental method with complete randomize design with 3 treatments and 3 times replications namely P1 (moringa leaves 0%), P2 (moringa leaves 5 %), and P3 (moringa leaves 10 %). Statistical analysis of organoleptic test about acceptability of colour, texture, and taste uses Friedman Rank test. It is obtained that sempol which gets addition moringa leaves P2 (moringan leaves 5%) can accept organoleptically. But it is needed to do research about early processing stage to eliminate the unpleasant aroma of moringa leaves.